2011
DOI: 10.1161/circulationaha.110.014324
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Cardiac Resynchronization Therapy in the Multicenter Automatic Defibrillator Implantation Trial With Cardiac Resynchronization Therapy (MADIT-CRT)

Abstract: on behalf of the MADIT-CRT Executive CommitteeBackground-We hypothesized that combined assessment of factors that are associated with favorable reverse remodeling after cardiac resynchronization-defibrillator therapy (CRT-D) can be used to predict clinical response to the device. Methods and Results-The study population comprised 1761 patients enrolled in the Multicenter Automatic Defibrillator Implantation Trial With Cardiac Resynchronization Therapy (MADIT-CRT). Best-subset regression analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
217
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(242 citation statements)
references
References 35 publications
17
217
2
6
Order By: Relevance
“…Other investigators also did not find gender or etiology, adjusted to LV volumes, to be independent predictors. 8 On the other hand, sub-analyses of randomized clinical trials have suggested that CRT has greater beneficial effects on LV function and/or prognosis in females 6,9,10,19 and in nonischemic etiology. 7,11 Of our patients, 34% were in atrial fibrillation, the most common arrhythmia in HF and associated with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators also did not find gender or etiology, adjusted to LV volumes, to be independent predictors. 8 On the other hand, sub-analyses of randomized clinical trials have suggested that CRT has greater beneficial effects on LV function and/or prognosis in females 6,9,10,19 and in nonischemic etiology. 7,11 Of our patients, 34% were in atrial fibrillation, the most common arrhythmia in HF and associated with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10 Park et al demonstrated that baseline LV volume was a predictor of echocardiographic CRT response. 8 Rickard et al 3 showed that the smaller the LV size, the greater the improvement in LVEF and all-cause mortality after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report on the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial, we noted a general effect of well-defined baseline variables, such as coronary or pulmonary disease and heart failure, that limited beneficial outcomes with all interventions tested [6]. Similar situations exist in trials employing implantable cardioverterdefibrillators (ICDs) for sudden death prophylaxis in patients with renal dysfunction and class IV heart failure [4,8]. Other baseline variables influence outcomes only with specific interventions, for example, amiodarone use in atrial fibrillation patients with preexisting or treated thyroid disease or high energy shocks in patients with impaired left ventricular function and comorbidities [6,7].…”
mentioning
confidence: 89%
“…Prophylaxis of sudden death events in clinical practice using implantable defibrillator devices in high-risk patients resulted in unused device therapy in a very large proportion of all recipients [3]. These non-uniform outcomes are also seen in cardiac resynchronization therapy and ablation of an increasingly broad spectrum of the AF population [4,5].…”
mentioning
confidence: 99%
“…A recent substudy of the Multicenter Automatic Defibrillator Implantation Trial-Cardiac Resynchronization Therapy (MADIT-CRT) population found 7 different patient characteristics that were most predictive of this positive response, with female gender conferring a greater degree of reverse remodeling and better outcomes with resynchronization therapy. 51 Menopause and Hormone Replacement Therapy After menopause, a woman's risk of HF rises exponentially. The loss of endogenous estrogen plays an important role in this increased risk.…”
Section: Hf Therapiesmentioning
confidence: 99%